Laboratório de didática e formação em serviço dos professores de biologia: um estudo de caso - Germano, Francisco Wagner da Costa (2019)
The present work is the result of an effort to identify the factors that influence the teacher training process as an educational and pedagogical qualification instrument, taking as a support the Laboratory of Didactics and Teacher Improvement - LDAD, of the State School of Professional Education Francisca Rocha Silva. This equipment aims to provide the schoolteachers with a structured, didactic, pedagogical and technically conducive environment for their in-service training. From this, the objective of this research is to analyze the contribution that the Laboratory of Didactics and Teaching Improvement provides for the improvement of the teaching of Biology teachers, through its qualification through the continuous training carried out in said environment. Firstly, the state of the question (EQ) was elaborated for which a mapping of the published works and the understandings on the theme of teacher services was elaborated, identifying titles and authors who wrote that could contribute to the creation of a bibliographical table with articles, theses, books and academic journals of national publication. For the EQ the starting point for research were the keywords: "teacher training in service", "teacher training" and "continuing teacher training". The research was structured by the exploratory method, of a qualitative nature, performed through an interview with open questions as an instrument to understand the teachers' perception regarding the contribution of the in-service training provided by the LDAD, through their participation in the study and research sessions; teaching methods and techniques; reflective analysis of teaching and re-dimensioning of teaching practice. The research has as a temporal limitation, the academic years of 2016 and 2017, period of insertion of LDAD in the EEPR Francisca Rocha Silva, in the municipality of Jaguaruana-CE, a teaching unit that delimits the environmental space. In analyzing the contribution that the Laboratory showed how important and feasible is the use of this didactic pedagogical tool for the improvement and professional qualification of the professors of the discipline of Biology of the institution, through the continuous training carried out in said environment. One of the impacts is to improve the technical conditions of teachers for the full exercise of their functions in the classroom. Finally, it was possible to create an educational platform called LDAD Virtual, to carry out the activities contained in the didactic project.